PERAN REGULATOR DALAM MENDORONG IMPLEMENTASI STANDAR AKUNTANSI SYARIAH PADA INDUSTRI PERBANKAN SYARIAH INDONESIA - Nisa, Raudhatun; Yani, Fitri (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the role of regulators in encouraging the implementation of Sharia accounting standards in the Islamic banking industry in Indonesia. The regulatory bodies involved include the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and the Sharia Supervisory Board (DPS). Using a qualitative descriptive approach with data collected from relevant books and academic journals, the results show that DSNMUI and DPS play an important role in developing Sharia accounting standards in Indonesia and strengthening the supervision of compliance with Sharia principles in the Islamic banking industry. The study recommends that DSNMUI and DPS continue to strengthen their roles and functions in facilitating the implementation of Sharia accounting standards in the Islamic banking industry